A breeding method for Ogura CMS restorer line independent of restorer source in Brassica napus - Wang, Xuesong; Liang, Xingyu; Wang, Rui; Gao, Yuan; Li, Yun; Shi, Haoran; Gong, Wanzhuo; Saleem, Saira; Zou, Qiong; Tao, Lanrong; Kang, Zeming; Yang, Jin; et al. (Frontiers in Genetics, 2025)
The Ogura cytoplasmic male sterility (CMS) line of Brassica napus has gained significant attention for its use in harnessing heterosis. It remains unaffected by temperature and environment and is thorough and stable. The Ogura cytoplasmic restorer line of Brassica napus is derived from the distant hybridization of Raphanus sativus L. and B. napus, but it carried a large number of radish fragments into Brassica napus, because there is no homologous allele of the restorer gene in B. napus, transferring it becomes challenging. In this study, the double haploid induction line in B. napus was used as the male parent for hybridization with the Ogura CMS of B. napus. Surprisingly, fertile plants appeared in the offspring. Further analysis revealed that the cytoplasmic type, ploidy, and chromosome number of the fertile offspring were consistent with the sterile female parent. Moreover, the mitochondrial genome similarity between the fertile offspring and the sterile female parent was 97.7% indicates that the cytoplasm of the two is the same, while the nuclear gene difference between fertile offspring and sterile female parent was only 10.33%, indicates that new genes appeared in the offspring. To further investigate and locate the restorer gene, the BSA method was employed to construct extreme mixed pools. As a result, the restorer gene was mapped to three positions: A09 chromosome 10.99–17.20 Mb, C03 chromosome 5.07–5.34 Mb, and C09 chromosome 18.78–36.60 Mb. The experimental results have proved that induction does produce restorer genes. The induction of the Ogura CMS restorer gene through DH induction line provides a promising new approach for harnessing heterosis in B. napus.